INTEGRATING DIGITAL FLIPPED CLASSROOM WITH STUDENT TEAM ACHIEVEMENT DIVISION APPROACH TO IMPROVE ENGLISH READING SKILLS - TIYAWONG, Apapan; Chankit, Mattana (Asian Interdisciplinary and Sustainability Review, 2024)
This quantitative research aimed to investigate integrating digital flipped classroom with student team achievement division (STAD) approach to improve English reading skills of undergraduate students and to compare the achievement pre-test and posttest of students in the experimental group. The third purpose was to compare the achievement pre-test and posttest of students in the control group and the last purpose was to compare the achievement in English Reading Skill between the experimental group and the control group. The sample was undergraduate students in Rajamangala University of Technology Tawan-ok, Thailand. They were divided into two group: 50 for experimental group and 50 for control group by purposive sampling who enrolled in English for study skills course. There were two equipment such as English reading program (3 lessons) and three lesson plans for STAD. The results found firstly students in experimental group who studied English reading program before doing STAD for improving their reading skills had higher academic achievement in posttest than the control group who hadn’t studied the English reading program before doing STAD in classroom with statistical significance at the level of 0.05. Secondly, students who studied STAD technique to develop English reading skills had significantly higher academic achievement after studying than before studying at the level of 0.05. Finally, the academic achievement of the experimental group was significantly higher than the academic achievement of the control group at the level of 0.05.